Deregulation of microRNAs expression and its role in Bcr-Abl+ cells resistance to TKI therapy - Coelho, Maria Gabriela Berzoti (2020)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm characterized by stem cell deregulation and increased myeloid proliferation without impairment of differentiation capacity. The hematopoiesis deregulation arises from the formation of a Bcr-Abl oncoprotein with constitutive tyrosine kinase (TK) activity, responsible for the malignant cell transformation. The tyrosine kinase inhibitors (TKI) therapy changed dramatically the CML natural history, promoting high rates of disease remissions in patients. However, at least 25% of CML patients are resistant to TKI therapy. Despite all the knowledge about the pathogenesis and progression of CML, the cellular and molecular mechanisms underlying the TKI-resistance are not fully understood. Therefore, we supposed that microRNAs deregulated expression contributes to IM-resistance in Bcr-Abl+ cells. MicroRNAs are small endogenous RNAs that regulate gene expression. The changes of microRNAs expression have been associated with the pathogenesis of different neoplasms, and the role of microRNAs in the development of resistance to drug-therapies was already demonstrated in a wide range of cancers. In this current investigation, we hypothesized that the inhibition of specific microRNAs could sensitize Bcr-Abl+ resistant cells to the TKI imatinib mesylate (IM) therapy. The expression of miR-125a-5p, miR-125b, and miR-132 was assessed in 61 CML patients, of which 10 samples were from newly diagnosed patients, 15 from patients in the advanced stages of the disease (accelerated phase and blast crisis), and 36 samples from patients in the disease remission after IM or dasatinib (DAS) therapy. The miR-125b was less expressed in the patients in the disease remission after DAS treatment than in the newly diagnosed patients and patients in the advanced stages. Other five microRNAs up-regulated in Bcr-Abl+ cells were selected using the NanoString\'s microRNA panel (miR-23a, miR-24, miR-155, miR-222, and miR-342). Then, the transient and stable inhibition of all the above mentioned microRNAs was performed in the IM-resistant Bcr-Abl+ cell line, LAMA-84R. The inhibition of miR-125a-5p, miR-132, and miR-23a did not sensitize the LAMA-84R cells to IM treatment. The inhibition of miR-125b, miR-24, miR-155, miR-222, and miR-342 promoted a modest increase of LAMA-84R cells sensitivity to the IM treatment. Additionally, the miR-222 and miR-342 overexpression in LAMA-84S, the sensitive counterpart of LAMA-84R, didn\'t promote the cells\' resistance to the IM treatment. A new approach was performed to select the microRNAs that are strongly associated with IM-resistance, the phenotypic screen based on the pLX-miR Library. After Next-Generation sequencing analysis, let-7e, miR-181a, miR-484, miR-616, and miR-96 were selected. These microRNAs expression was assessed in the patients groups. All the five microRNAs were less expressed in the patients in the disease remission after IM treatment than in the newly diagnosed patients. Currently, we are validating the results obtained from the phenotypic screen by the individual knockout of the five microRNAs through the CRISPR-Cas9 gene-editing system. The results will contribute to elucidate the mechanisms involved in CML resistance to imatinib mesylate and to describe new therapeutic targets that are independent of the Bcr-Abl oncoprotein.